The role of intelligence and temperamental traits in predicting reaction times in movement anticipation tasks: a preliminary study using the PAMT Test2Drive computer test - Monika Maria Małkiewicz (Nofer Institute of Occupational Medicine, 2020)
Background The objective of the present work was to determine whether fluid intelligence scores and individual temperamental traits may be used to predict drivers' reaction times in movement anticipation tasks. Material and Methods The study encompassed 68 young female drivers (aged 20-26 years), who had received their driver's licenses at least 2 years prior. Anticipatory performance was evaluated using the Perception Anticipation Movement Test (PAMT) consisting of 3 sets of computer tasks differing in the speed of the moving objects. The level of fluid intelligence was determined using Raven's Standard Progressive Matrices, and the temperamental traits with the Pavlovian Temperament Survey. Results Intelligence was found to be significantly correlated with reaction time only in the second PAMT task set, for which it was also a good predictor. Findings suggested that a higher level of fluid intelligence in young female drivers was associated with longer reaction times in the movement anticipation task with objects moving at the medium speed level. Temperamental traits did not correlate with reaction times in all movement anticipation tasks, and they did not explain the participants' performance in the PAMT task sets. Conclusions This study expands the current literature by assessing the relationship between fluid intelligence, temperamental traits and reaction times in movement anticipation tasks with objects moving at different speeds. The outcomes of this study are discussed together with those of previous research. Med Pr. 2020;71(4):421-7